Pelatihan Pola Zero Waste Untuk Mengurangi Limbah Kain - Romadhona Chusna Tsani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Early The fashion industry in Indonesia is one of the contributors to fabric waste which is difficult to handle, requires special handling so that fabric waste can decompose or become a multi-purpose product. The Zero Waste pattern is a technique in making clothing patterns that places the pattern effectively without leaving fabric residue. The Zero Waste pattern can be used in making clothes and trousers so it is effective in reducing fabric waste. The target of this training is class 2 and class 3 Fashion Design Vocational School students who are taking pattern subjects. This training aims to provide additional knowledge to students in the field of fashion pattern making. This training is expected to be able to add new experiences so as to improve the skills and competencies of Fashion Design students. The method used is to provide insight and training in Zero Waste pattern making to vocational school students. This training produces trousers products using the Zero Waste pattern. Pants products with the Zero Waste pattern can become a trend for contemporary young people and leave no waste.